2013
DOI: 10.1039/c3cc40895g
|View full text |Cite
|
Sign up to set email alerts
|

Long-lived superhydrophobic colorful surfaces

Abstract: Rough structures created from bulk materials at the surface could have superior durability. Superhydrophobic colorful surfaces were fabricated through chemical etching of the fiber surfaces, followed by diffusion of fluoroalkylsilane into fibers. The obtained superhydrophobic textiles show strong durability against severe abrasion, long-time laundering, and boiling water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 18 publications
1
63
1
Order By: Relevance
“…Because carboxylic and hydroxyl groups are water absorbing, their presence makes the treated fibers have a hydrophilic surface. Using NaOH to improve the water wettability of polyester fabric has been reported by other researchers, [46][47][48] despite the treatment method is slightly different. SU-8 solution was then deposited on one side of the NaOH pre-treated fabric using an electrospraying technique.…”
Section: Resultsmentioning
confidence: 92%
“…Because carboxylic and hydroxyl groups are water absorbing, their presence makes the treated fibers have a hydrophilic surface. Using NaOH to improve the water wettability of polyester fabric has been reported by other researchers, [46][47][48] despite the treatment method is slightly different. SU-8 solution was then deposited on one side of the NaOH pre-treated fabric using an electrospraying technique.…”
Section: Resultsmentioning
confidence: 92%
“…In order to improve the compatibility of PET fibers with the SiO 2 nanoparticles, the textiles were treated with NaOH. Previous studies [30][31][32] showed that this treatment can generate chemical and morphological changes in the PET textile. Morphological changes roughened the fiber surfaces (Fig.…”
Section: Coating Fibers With Hydrophobic Sio 2 Solmentioning
confidence: 98%
“…The abrasion resistance was evaluated using a friction instrument for textiles according to the method reported [30]. Samples were endured to normal pressure (45 kPa), and slid back and forth on a common nylon textile with a moving path of 200 mm in each cycle.…”
Section: Coating Fibers With Hydrophobic Sio 2 Solmentioning
confidence: 99%
“…Wenzel and Cassie-Baxter models explained this transformation mechanism. Noticeably, the superhydrophobic GFRP surfaces are chemically stable with organic solvents (toluene, acetone, tetrahydrofuran, and ethanol) and water droplets with different pH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The superhydrophobicity of GFRP can be maintained for 6 months or more.…”
Section: Discussionmentioning
confidence: 96%
“…Superhydrophobic surfaces, which exhibit a water CA greater than 150°, have received dramatic attention during the past years [1][2][3][4][5]. Superhydrophobic surfaces have many potential industrial applications, such as the surface self-cleaning [6], oil/water separation [7], efficient microfluidic devices [8], anticorrosive coatings [9], and so on.…”
Section: Introductionmentioning
confidence: 99%